2012
DOI: 10.1002/esp.3353
|View full text |Cite
|
Sign up to set email alerts
|

Measuring bluff erosion part 1: terrestrial laser scanning methods for change detection

Abstract: Human activities influence watershed sediment dynamics in profound ways, often resulting in excessive loading of suspended sediment to rivers. One of the primary factors limiting our ability to effectively manage sediment at the watershed scale has been our inability to adequately measure relatively small erosion rates (on the order of millimeters to centimeters per year) over annual and sub‐annual time scales on spatially‐extensive landforms, such as river banks and bluffs. Terrestrial laser scanning (TLS) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 31 publications
2
55
0
Order By: Relevance
“…Jaboyedoff et al, 2012;Barnhart and Crosby, 2013) and investigating Earth surface processes (e.g. Schürch et al, 2011;Montreuil et al, 2013;Day et al, 2013). In these applications, TLS data usually need to be transformed into an external coordinate system for data fusion or the derivation of surface movement.…”
Section: : Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaboyedoff et al, 2012;Barnhart and Crosby, 2013) and investigating Earth surface processes (e.g. Schürch et al, 2011;Montreuil et al, 2013;Day et al, 2013). In these applications, TLS data usually need to be transformed into an external coordinate system for data fusion or the derivation of surface movement.…”
Section: : Introductionmentioning
confidence: 99%
“…This approach has also widely been adopted by researchers (e.g. Barnhart andCrosby, 2013, Lague et al, 2013;Montreuil et al, 2013;Day, et al, 2013). They are single and spatial uniform statistics per point cloud.…”
Section: : Introductionmentioning
confidence: 99%
“…Meter-and sub-meter-scale time-varying processes, often derived from TLS, have been quantified in the response of point bar and bank morphodynamics (Lotsari et al, 2014) and in the formation of micro-topography due to feedbacks with biota (e.g., Roering et al, 2010;Harman et al, 2014). Examples of larger scale change detection applications, typically ALS-derived, include measuring changes in stream channel pathways resulting from Holocene climate change and anthropogenic activities (e.g., Day et al, 2013;Kessler et al, 2012;James et al, 2012;Belmont et al, 2011), rates of change in migrating sand dunes (Pelletier, 2013), the influence of lithology and climate on hillslope form (e.g., Marshall and Roering, 2014;Hurst et al, 2013;Perron et al, 2008;West et al, 2014), and channel head formation (e.g., Pelletier et al, 2013;Pelletier and Perron, 2012;Perron and Hamon, 2012). Automated tools to identify geomorphic features (e.g., floodplains, terraces, landslides) and transitional zones (e.g., hillslope-to-valley, floodplain-tochannel) have been used in conjunction with high-resolution elevation data sets from lidar, including Geonet 2.0 (Passalacqua et al, 2010), ALMTools (Booth et al, 2009), and TerrEX (Stout and Belmont, 2014).…”
Section: Advances In Geomorphology Using Lidarmentioning
confidence: 99%
“…Guarnieri et al (2009) carried out research into the retrieval of small-relief marsh morphology from TLS, and found that the vegetation-induced uncertainty was in the order of a few centimetres. Day et al (2013) investigated the use of TLS for measuring bluff erosion and discussed the effect of ground vegetation in this application. Pirotti et al (2013) investigated the use of a multi-return terrestrial laser scanner in measuring vegetated ground, and proposed a work-flow for identifying ground points and deriving digital terrain and surface models.…”
Section: Introductionmentioning
confidence: 99%